(untitled) (Rudarsko-geološko-naftni zbornik, 2024)
Chemical Enhanced Oil Recovery (CEOR) methods are garnering significant global attention in light of the substantial decline in available oil resources. These techniques are employed to enhance oil recovery from various types of reservoirs by influencing critical parameters, such as the mobility of trapped oil within the reservoir rock’s pore network, interfacial tension (IFT) between water and oil, wettability and the spreading behaviour of chemical solutions on rock surfaces. Nanoparticles (NPs) represent novel agents in CEOR processes, offering promising contributions owing to their enhanced surface activity at the crude oil-brine-rock interface and their impact on disjoining pressure. Incorporating polymers into nanofluids improves the dispersion stability of NPs, extending their capability for wettability alteration and achieving faster equilibrium states compared to polymer-free nanofluids. Experimental investigations involved the use of various combinations of tragacanth, TiO2, and Al2O3 with water at different temperatures for oil recovery. The results revealed that the tragacanth + Al2O3 combination at 50°C exhibited the highest recovery rate of 16.57%. The most significant decrease in interfacial tension was observed at 25°C (16.75%), while the most favourable characteristics for reducing interfacial tension (9.38%) were observed at 50°C compared to 75°C (18.3%). Tragacanth demonstrated the highest viscosity among the tested substances at 25°C, with a measured value of 4.27 centipoise (cP), while reductions of 2.87 cP and 1.45 cP were observed at 50°C and 75°C, respectively. According to the obtained results, it is appropriate to say that the solution of tragacanth + Al2O3 has shown the best performance in increasing EOR and decreasing the interfacial tension in sand-pack flooding.